Poisoned legacy : the decline and fall of the Nineteenth Egyptian Dynasty - Dodson, Aidan, 1962- (The American University in Cairo Press, 2010)
Sethy I and Rameses II's promotion of a concept of a wider 'royal family' may have sown the seeds for the conflicts among their descendants. Aidan Dodson explores the mysteries of the origins of the usurper-king Amenmeses and the career of the 'king-maker' of the period, the chancellor Bay.